Decoding Pragmatic Force: A Cross-Linguistic Analysis of Istifham Taqriri in Juz ‘Amma Translations - Divta Ayu Putri Pertiwi; Sofia Binti Salim Ghanim; Agung Pranoto Kadiatmaja (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examines the pragmatic function of istifhām taqrīrī (rhetorical interrogatives) in Juz ‘Amma of the Qur’an and its representation in English translations. Unlike ordinary interrogatives that seek information, istifhām taqrīrī serves as a rhetorical device to affirm truths, reinforce meaning, and prompt implicit acknowledgment (iqrār) from the audience. Despite its importance, systematic studies on this form, particularly from a pragmatic and translation perspective, remain limited. This research adopts a descriptive qualitative approach using library research. The primary data consist of Qur’anic verses from Juz ‘Amma, while secondary data are derived from classical works of balāghah and relevant scholarly studies. Data are analyzed through content analysis using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings show that istifhām taqrīrī primarily functions as taqrīr (affirmation) and ta’kīd al-ḥaqīqah (emphasis of truth), while functions such as tasliyah appear contextually. However, English translations often reduce rhetorical interrogatives into neutral questions or declarative statements, resulting in pragmatic loss and weakened persuasive impact. Therefore, a pragmatic-functional translation approach is needed.